2020
DOI: 10.1096/fj.201903047r
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA 000554 represses epithelial‐mesenchymal transition in breast cancer by regulating microRNA‐182/ZFP36 axis

Abstract: Increasing evidence indicates that circular RNAs (circRNAs) play a crucial role in regulating microRNAs (miRs) and mRNAs during breast cancer (BC) progression. Based on the in silico analysis of circRNA/miR/mRNA in BC, we aim to define an important role of circRNA_000554 in BC in relation to miR‐182 and zinc finger protein 36 (ZFP36). Low expression of circRNA_000554 and ZFP36, and high miR‐182 expression were determined in the clinical BC tissues. CircRNA_000554 acted as a sponge of miR‐182, and miR‐182 direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Cut-off values of high or low circRNA expression were mostly median or mean.The range of mean duration of follow□up was from 30 to 250 months.Moreover,Detection methods of circRNA expression were mainly quantitative real□time polymerase chain reaction (RT□PCR).Sample types were almost from tissues. As for clinical outcome indicators, 27 studies[10, 11, 13-34],[35-37]included overall survival (OS), 5 studies[19, 29, 31, 33, 38]included disease-free survival (DFS).As shown in Table 3, nineteen types of circRNAs were recognized as tumor promoters and nine were tumor suppressors. 28 circrnas have corresponding targets and can promote or inhibit the proliferation, invasion and metastasis of breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cut-off values of high or low circRNA expression were mostly median or mean.The range of mean duration of follow□up was from 30 to 250 months.Moreover,Detection methods of circRNA expression were mainly quantitative real□time polymerase chain reaction (RT□PCR).Sample types were almost from tissues. As for clinical outcome indicators, 27 studies[10, 11, 13-34],[35-37]included overall survival (OS), 5 studies[19, 29, 31, 33, 38]included disease-free survival (DFS).As shown in Table 3, nineteen types of circRNAs were recognized as tumor promoters and nine were tumor suppressors. 28 circrnas have corresponding targets and can promote or inhibit the proliferation, invasion and metastasis of breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the upregulation of CIRc_0103552 can also promote cell growth, clonal formation, migration and invasion, and reduce apoptotic cells. A recent study [11]showed that the expression of circRNA_000554 in BC tissues was significantly lower than that in normal tissues, and the survival time of hsa_circRNA_000554 with low expression was shorter than that of circRNA_000554 with overexpression. In addition, they found that circRNA_000554 with overexpression inhibited EMT, cell invasion and migration during breast cancer by decreasing Mir-182 and increasing ZFP36.…”
Section: Introductionmentioning
confidence: 99%
“…Both CircRNAs 000554 and circRNA_0025202 can sponge miR-182 to regulate the expression of ZNF36 and FOXO3a, respectively, and thus inhibit cellular proliferation, invasion, migration, and sensitivity to chemotherapy agents (155,156). Similarly, circRNA-0001283 functions to sponge miR-187 to suppress HIPK3 expression, thus inhibiting the proliferation and invasion and promoting the apoptosis of breast cancer cells (157).…”
Section: Cernasmentioning
confidence: 99%
“…miRNAs, a class of non-coding RNA approximately 22 nt in length, exert crucial roles in the initiation and progression of cancer, acting either as oncomiRs or as tumor suppressors through several molecular mechanisms (Markopoulos 2017 ). miR-182 inhibition contributes to suppressed epithelial-mesenchymal transition, invasion and migration of breast cancer cells in vitro along with tumor growth in vivo (Mao 2020 ). TargetScan website predicted the binding sites between miR-182-5p and CKLF-like MARVEL transmembrane domain-containing 7 (CMTM7), a member of the CMTM family playing key roles in the occurrence and progression of cancer.…”
Section: Introductionmentioning
confidence: 99%